Opioid overdose prevention education for medical students: Adopting harm reduction into mandatory clerkship curricula. Issue 1 (2nd January 2020) - Oldfield, Benjamin J.; Tetrault, Jeanette M.; Wilkins, Kirsten M.; Edelman, E. Jennifer; Capurso, Noah A.
Abstract: Background: Opioid overdose deaths constitute a public health crisis in the United States. Strategies for reducing opioid-related harm are underutilized due in part to clinicians' low knowledge about harm reduction theory and limited preparedness to prescribe naloxone. Educational interventions are needed to improve knowledge and attitudes about, and preparedness to address, opioid overdoses among medical students. Methods: Informed by the Department of Veterans Affairs' Overdose Education and Naloxone Distribution (OEND) program and narrative medicine, we developed and led a mandatory workshop on harm reduction for clerkship medical students. Using validated scales, we assessed students' knowledge and attitudes about, and preparedness to address, opioid overdoses before the workshop and 6 weeks after. Results: Of 75 participating students from February through December 2017, 55 (73%) completed pre-workshop and 38 (51%) completed both pre- and post-workshop surveys. At baseline, 40 (73%) encountered patients with perceived at-risk opioid use in the previous 6 weeks, but only 11 (20%) recalled their teams prescribing naloxone for overdose prevention. Among those completing both surveys, knowledge about and preparedness to prevent overdose showed large improvement (Cohen's d  = 0.85, P  < .001; Cohen's d  = 1.24, P  < .001, respectively) and attitudes showed moderate improvement (Cohen's d  = 0.32, P = .04). Discussion: Educational interventions grounded in harm reduction theory can increase students' knowledge and attitudes about, and preparedness to address, opioid overdoses.